The Determinant Factor of Employee Engagement at Palm Oil Plantations Company in Central Kalimantan Province - Veritia, Veritia; Moeins, Anoesyirwan; Sunaryo, Widodo (Eastasouth Institute, 2024)
With today's tougher business competition, many companies have realized how important human resources (HR) are. Organizational culture, knowledge management, and employee engagement are the keys to the success of human resources. This study aims to see the influence of organizational culture, knowledge management on employee engagement. This type of research uses mixed methods. Mixed Methods is a research method that combines quantitative research and qualitative research. In this research method using a sequential explanatory combination, starting with using quantitative methods and then expanding with qualitative and comparing the average results of both. In this study using a linearity test which is used to identify the regression model of the independent variable on the dependent variable, the study focused on a population of 1960 companies and 321 employees from the Palm Oil Company Group. The sample size consisted of 179 employees. The findings of the study are: 1) Organizational culture positively impacts employee engagement in Palm Oil Companies in Central Kalimantan Province, and 2) Knowledge management also has a positive effect on employee engagement in Palm Oil Companies in Central Kalimantan Province.